Effects in air-exposed corn silage of medium chain fatty acids on select spoilage microbes, zoonotic pathogens, and in vitro rumen fermentation. Issue 1 (2nd January 2023) - Arzola-Alvarez, Claudio; Ruiz-Barrera, Oscar; Castillo-Castillo, Yamicela; Ontiveros, Marina; Fonseca, Mozart; Jones, Barbara W.; Smith, William B.; Hume, Michael E.; Harvey, Roger; Poole, Toni L.; Anderson, Robin C.; Arzola-Rubio, Alejandro; et al.
Abstract: Medium chain fatty acid (MCFA) treatment (0.75% C6, hexanoic; C8, octanoic; C10, decanoic; or equal proportion mixtures of C6:C8:C10:C12 or C8:C10/g; C12 = dodecanoic acid) of aerobically-exposed corn silage on spoilage and pathogenic microbes and rumen fermentation were evaluated in vitro . After 24 h aerobic incubation (37 °C), microbial enumeration revealed 3 log10 colony-forming units (CFU)/g fewer ( P  = 0.03) wild-type yeast and molds in C8:C10-treated silage than controls. Compared with controls, wild-type enterococci decreased ( P  < 0.01) in all treatments except the C6:C8:C10:C12 mixture; lactic acid bacteria were decreased ( P  < 0.01) in all treatments except C6 and the C6:C8:C10:C12 mixture. Total aerobes and inoculated Staphylococcus aureus or Listeria monocytogenes were unaffected by treatment ( P  > 0.05). Anaerobic incubation (24 h at 39 °C) of ruminal fluid (10 mL) with 0.02 g overnight air-exposed MCFA-treated corn silage revealed higher hydrogen accumulations ( P  = 0.03) with the C8:C10 mixture than controls. Methane, acetate, propionate, butyrate, or estimates of fermented hexose were unaffected. Acetate:propionate ratios were higher ( P  < 0.01) and fermentation efficiencies were marginally lower ( P  < 0.01) with C8- or C8:C10-treated silage than controls. Further research is warranted to optimize treatments to target unwanted microbes without adversely affecting beneficial microbes.